Universal classifications, national approaches and specific situations: a comparative study on the conceptualization of nodding syndrome in Uganda and Tanzania. Issue 2 (4th May 2019) - van Bemmel, Karin; van der Weegen, Kim
ABSTRACT: This paper presents a comparative study on conceptualizations of the poorly understood nodding syndrome (NS) in Uganda and Tanzania. NS has been constructed as a biomedical category to serve global health discourse as well as national contexts of managing the condition. The paper looks into the shifting meanings and conceptualizations of NS in the affected areas of Kitgum (UG) and Mahenge (TZ) district. The perceived universality of biomedical classifications is problematized as conflicting with the specific contexts of lucluc and kifafa cha kusinzia . Reconciliation proves to be challenging, poignantly evoking the cultural construction as such of any medical condition.